The Transformation of the Agricultural Administration and Associations in East Germany Before and After Unification: Are there lessons for the Korean Peninsula? - Axel Wolz (한국농촌경제연구원, 2012)
With the collapse of the socialist regime in East Germany in late 1989 and the rising political call for unification in early 1990, a radical and abrupt change of the institutional structure became necessary. The (agricultural) administration had to be totally restructured. This included not only substance, functions and tasks which had to be adjusted, similar to all other transition economies, to the market-economic and pluralistic democratic system, but also the whole administrative set-up had to be re-established in line with the West German system (territorial re-organization). Hence, a new administrative system had to be built up from scratch, while simultaneously the socialist one had to be dismantled in a very short period. However, different to other transition economies, there had been strong support from the West in re-organizing the administrative set-up. Overall, this institutional change seems to have been accomplished successfully as billions of Deutsch Marks could be processed by the agricultural administration in 1990 in order to avoid an imminent collapse of the agricultural sector. In addition, the organizations representing the agricultural population had to be re-organized. The re-organization of the German Farmers’ Union is of special prominence as both German parts were representing completely different agricultural systems. This is the only important organization at national level where East Germans could stay in decision-making positions after unification which had severe repercussions when shaping transformation policies affecting the agricultural sector during the 1990s.
Keywords: transition; agricultural administration; farmers’ union; unification; Germany; transition; agricultural administration; farmers’ union; unification; Germany